Crossing borders in African literatures - Ce, Chinenye; Smith, Charles (African Books Network., 2015)
Crossing Borders showcases intellectual attempts to commit the process of African interrogation of postcoloniality and postmodernity to the exploration of perspectives on black identities and interactions of contemporary cultural expressions beyond the borders of Africa and across the Atlantic. We have particularised on theoretical and critical perspectives that show how the controversial influence of westernisation of Africa has demanded remedial visions and counteractive propositions to the cycle of abuses and fragmentation of the continent. We have consequently distilled some very significant historic and informative insights on modern African and black literary traditions methodically espoused to articulate the greater unity in the diversities, fusions and hybrids that have been embedded in the external and subjective realities of our universe.